Pengaruh Profitabilitas, Leverage, Invesment Oppurtunity Set dan Kualitas Laba Terhadap Nilai Perusahaan (Studi Pada Perusahaan Sub Sektor Perbankan Yang Terdaftar Dibursa Efek Indonesia Periode 2020-2023) - Tri Amanda, Shinta; Syafei, Jasmina; Delmi Yetti, Febri (Basecamp Economics PubMed, 2024)
This This research aims to determine the influence of profitability, leverage, investment opportunity set and profit quality on company value in banking sub-sector companies listed on the Indonesia Stock Exchange (BEI) for the 2020-2023 period. Data analysis uses the classic assumption test and hypothesis testing uses panel data regression analysis using the eviews version 12 tool. The research results show that the investment opportunity set is proven to have an effect on company value. Meanwhile, profitability, leverage and earnings quality are proven to have no effect on company value. The magnitude of the influence exerted by these variables together on the dependent variable is 67%, while the remaining 33% is influenced by other variables not examined in this research.